2010
DOI: 10.1007/s12011-010-8650-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Serum and Hair Concentrations of Minerals and their Relationship with Serum Lipids and Glucose Levels in Hypertensive and Obese Patients with Insulin Resistance

Abstract: Inadequate minerals intake, as well as disruption of some metabolic processes in which microelements are cofactors, are suggested to lead to the development of hypertension. The role of minerals in the pathogenesis of hypertension still remains to be explained. In the present study, we sought to determine associations between serum and hair mineral concentrations and serum lipids and glucose levels. Forty obese hypertensive subjects with insulin resistance and 40 healthy volunteers were recruited in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
39
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 54 publications
8
39
0
7
Order By: Relevance
“…This is the first study with comprehensive data on toxic and essential elements in the scalp hair samples of diabetic and referent subjects of two countries (Pakistan and Ireland). The concentrations of essential trace and toxic elements in scalp hair samples of the Irish referent subjects were close to those reported for other European [57][58][59][60][61][62][63][64][65], American [66][67][68][69] and Australian [70] countries (Table 7). The concentrations of Cd and Pb in Pakistani referents were almost higher than in European countries, which are in agreement with the studies carried out in Asia [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85], and African countries [86][87][88][89][90] (Table 7).…”
Section: Discussionsupporting
confidence: 81%
“…This is the first study with comprehensive data on toxic and essential elements in the scalp hair samples of diabetic and referent subjects of two countries (Pakistan and Ireland). The concentrations of essential trace and toxic elements in scalp hair samples of the Irish referent subjects were close to those reported for other European [57][58][59][60][61][62][63][64][65], American [66][67][68][69] and Australian [70] countries (Table 7). The concentrations of Cd and Pb in Pakistani referents were almost higher than in European countries, which are in agreement with the studies carried out in Asia [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85], and African countries [86][87][88][89][90] (Table 7).…”
Section: Discussionsupporting
confidence: 81%
“…Together, these cells produce unique substances, i.e., leptin, adiponectin, and resistin, which contribute to the para-and autoendocrine regulation of lipid metabolism (21,28). Limited epidemiological studies have linked aberrant trace mineral metabolism with adipose pathology; e.g., obesity is clinically correlated to deficiencies in iron, calcium, and zinc (18,19,49,50). Zinc was first thought to be involved in metabolic activity of adipocytes through insulin-like effects (36) and through its inherent antioxidant properties (16).…”
mentioning
confidence: 99%
“…According to our knowledge of the literature, many previous studies have examined the relationship of obesity or fat tissue and micro elements, mostly to investigate the effect of their use as supplements at weight-, fat tissue-, and obesityrelated molecule levels, whereas others have addressed the tissue or serum levels of obese individuals. [4,5,8,9,[45][46][47]. Of course, elements rarely enter the body in a pure form or by themselves, meaning that to accurately gauge the effect of trace elements on adipose tissue or the formation of fat tissue, the effect of water-the most important reservoir of minerals-on the formation of fat tissue needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the metabolism of carbohydrates and fats in humans is connected with zinc, copper and iron; and obesity's emergence could implicitly relate to disturbances in homeostasis [7]. For instance, several epidemiological studies have found a negative correlation between cellular zinc levels and the prevalence of obesity [8,9], whereas others have reported linkage between obesity and serum copper levels [10,11]. Abnormal cellular chromium, selenium, iron and other mineral concentrations have been reported in obese patients as well [12,13].…”
Section: Introductionmentioning
confidence: 99%